SUBJECT-LANGUAGE INTEGRATED LEARNING (CLIL) OF RUSSIAN AS A FOREIGN LANGUAGE - Bozorov Pulat Farhodovich (The Conference Hub, 2025)
When using the CLIL methodology, students are given the opportunity to study one or more academic disciplines in a foreign language. It is not assumed that students can speak a professional foreign language before starting to study a specialized subject. They study the language at the same time as the specialized subject [Baturina, 2017, p. 10]. In the context of CLIL, the language used as a medium of instruction can be either a foreign language, a second state language, or a language of a national minority [Grigoryeva, Yakhina, 2017, p. 485]. As a rule, the language of instruction is a foreign language that is rarely or never used in a social context outside the classroom. Classroom lessons form the main, and often the only, environment in which students can use the language they are studying [Filipovich, 2015, p. 75].